Pore‐Scale Distribution of Mucilage Affecting Water Repellency in the Rhizosphere - Benard, P. (2020)
This hypothesis was confirmed by microscope images and contact angle measurements. We measured the initial contact angle of quartz sand (0.5–0.63‐ and 0.125–0.2‐mm diameter), silt (36–63‐μm diameter), and glass beads (0.1–0.2‐mm diameter) mixed with varying amounts of chia (Salvia hispanica L.) seed mucilage (dry content range 0.2–19 mg g−1) using the sessile drop method. We observed a threshold‐like occurrence of water repellency. At low mucilage contents, the water drop infiltrated within 300 ms. Above a critical mucilage content, the soil particle–mucilage mixture turned water repellent. The critical mucilage content decreased with increasing soil particle size. Above this critical content, mucilage deposits have the shape of hollow cylinders that occupy a large fraction of the pore space. Below the critical mucilage content, mucilage deposits have the shape of thin filaments. This study shows how the microscopic heterogeneity of mucilage distribution impacts the macroscopic wettability of mucilage‐embedded soil particles.